Attitude towards Oral Health at Various Colleges of the University of Zagreb: A Pilot Study - Anja Ivica; Nada Galić (University of Zagreb. School of Dental Medicine, 2014)
Purpose: The aim of this study was to compare the oral status of three various groups of students: students of the School of Dental Medicine, students of technical sciences and students of humanities. Material and methods: Research included 58 students of the University of Zagreb. They answered 3 questions: how often they brush their teeth, how often they visit their dentist and how important dental health is to them. After a standard dental check-up we calculated the DMFT index. They were given an indicator for plaque Mira-2-Ton® (Hager Werken, Duisburg, Germany) and we calculated the plaque index. For statistical analysis the ANOVA test was used. Results: Students of the School of Dental Medicine had a lower plaque index than other students and this was statistically significant (p=0.0018; f=7.14). They also had a lower DMFT index, but it was not statistically significant (p=0.1004; f=2.4). 83% of students said that they brushed their teeth 2-3 times a day. Only 17% of all students brush their teeth more than 3 times a day and they are all students of the School of Dental Medicine (21% of them). Perception of oral health is on a high level, but perception of oral disease is not. The social approval of the answer was also an important factor. Conclusion: Students of the School of Dental Medicine are an illustrative example of improving our habits due to education.